We are invited to imagine: using a literary text to encourage cross-cultural dialogue about citizenship. Issue 4 (3rd July 2020) - Varga, Zoltan; McGuinn, Nicholas; Naylor, Amanda; Rimmereide, Hege Emma; Syed, Ghazal Kazim
ABSTRACT: Using William Golding's Lord of the Flies as a stimulus, researchers from Norway, Pakistan and the United Kingdom explored the potential of a literary text to encourage intercultural dialogue. The innovative research method used was to combine Literature Circles and Google Documents to provide a platform for asynchronous online exchange between three cohorts of students in higher education. The authors' analysis of the data suggested differences between those students who regarded the text as a living document speaking directly to their personal experiences of citizenship issues and those for whom the novel remained a historical document, removed from their lived experience. The authors contend that this research can contribute original and significant insights to the literature on teaching citizenship through literary texts such as the relationship between text choice and context, models of international collaboration at the higher education level and contrasting approaches towards citizenship and reading.